2017
DOI: 10.5588/ijtld.16.0515
|View full text |Cite
|
Sign up to set email alerts
|

Immune thrombocytopenia secondary to tuberculosis: a case and review of literature

Abstract: Immune thrombocytopenia (ITP) is an auto-immune condition that results in isolated thrombocytopenia associated with possibly lethal haemorrhage. In its secondary form, ITP can be triggered by many infectious and non-infectious conditions. Secondary ITP associated with tuberculosis (TB) has rarely been described in the literature. We report on a 22-year-old patient presenting with hypermenorrhoea and petechiae due to ITP secondary to tuberculous lymphadenitis. Normalisation of thrombocytopenia was only achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…While anemia is seen in most miliary TB patients, only up to one quarter have lymphopenia or thrombocytopenia as well [ 24 ]. Thrombocytopenia in TB can result from immune-mediated destruction, hypersplenism and infiltration of the bone marrow [ 25 ]. While ferritin is usually moderately increased in TB, values in excess of 10,000 ng/mL have been described in miliary TB [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…While anemia is seen in most miliary TB patients, only up to one quarter have lymphopenia or thrombocytopenia as well [ 24 ]. Thrombocytopenia in TB can result from immune-mediated destruction, hypersplenism and infiltration of the bone marrow [ 25 ]. While ferritin is usually moderately increased in TB, values in excess of 10,000 ng/mL have been described in miliary TB [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated thrombocytopenia in patients with TB is rare and hypothesized to be a secondary ITP. One review identified only 50 cases of secondary ITP associated with TB between 1964 and 2016 [7]. Anti-TB drug-induced thrombocytopenia could be caused by isoniazid, rifampicin or both, where autoimmune-mediated rifampicin is the most common [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 50 cases were summarized by Weber at al. In 2017 Pulmonary TB represented the most common clinical presentation with occurrences of 41% of in all cases which was followed equally at 21% by disseminated TB and the remaining patients had extrapulmonary TB (EPTB) at various sites [32].…”
Section: Discussionmentioning
confidence: 99%